Plastic potential: how the phenotypes and adaptations of pathogens are influenced by microbial interactions within plants. (August 2017) - O'Keeffe, Kayleigh R; Carbone, Ignazio; Jones, Corbin D; Mitchell, Charles E
Highlights: Individual plant pathogens respond plastically to within-host microbial interactions. Within-host microbial interactions may impact pathogen population dynamics. Cross-level studies will elucidate connection between plastic and genetic responses. Abstract : Predicting the effects of plant-associated microbes on emergence, spread, and evolution of plant pathogens demands an understanding of how pathogens respond to these microbes at two levels of biological organization: that of an individual pathogen and that of a pathogen population across multiple individual plants. We first examine the plastic responses of individual plant pathogens to microbes within a shared host, as seen through changes in pathogen growth and multiplication. We then explore the limited understanding of how within-plant microbial interactions affect pathogen populations and discuss the need to incorporate population-level observations with population genomic techniques. Finally, we suggest that integrating across levels will further our understanding of the ecological and evolutionary impacts of within-plant microbial interactions on pathogens.